2003
DOI: 10.1177/153857440303700606
|View full text |Cite
|
Sign up to set email alerts
|

Lesser Saphenous Vein Thrombophlebitis: Its Natural History and Implications for Management

Abstract: Little attention has been given to superficial thrombophlebitis and particularly to lesser saphenous vein thrombophlebitis (LSVT) by vascular surgeons. A prospective nonrandomized study was conducted to assess LSVT's potential association with deep venous thrombosis (DVT) as well as its natural history. Between January 1994 and December 1995, the authors reviewed 33 cases of LSVT detected by duplex scanning in 32 patients at their institution's vascular laboratory. Combined LSVT/DVT was treated with heparin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 8 publications
0
16
0
2
Order By: Relevance
“…Thus, 22 studies with a total of 4379 SVT patients were included in the meta‐analysis, 21 reporting data on the prevalence of DVT, and 11 reporting data on the presence of PE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, 22 studies with a total of 4379 SVT patients were included in the meta‐analysis, 21 reporting data on the prevalence of DVT, and 11 reporting data on the presence of PE.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐one studies reported on 4358 SVT patients screened for the presence of DVT. As reported in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Specimens retrieved from patients with AVF restenosis more frequently contained apoptosis foci than specimens of primary atherosclerotic lesions (19). The adventitia of varicose vein specimens showed lack of immunopositivity for Bax, while atherosclerotic lesions of primary and restenotic types showed a lack of immunopositivity for Bcl-2 (13,19-22). cfDNA released from blood cells by ongoing apoptosis was abundantly present in the plasma of hemodialysis patients (23).…”
Section: Discussionmentioning
confidence: 97%
“…Consequently, the wearing of inflight compression stockings may be a rare cause of superficial thrombophlebitis which may predispose to deep vein thrombosis in up to 42% of cases. 3 There is considerable public concern about deep vein thrombosis occurring during flights and patients in our outpatient clinic frequently enquire about wearing inflight stockings. By identifying this possible complication, we may be better able to discuss the benefits and risks of wearing the inflight compression stockings with our patients.…”
Section: Discussionmentioning
confidence: 99%